Cancer suspicion, referral to cancer patient pathway and primary care interval: a survey and register study exploring 10 different types of abdominal cancer. (27th April 2021) - Jessen, Nanna H; Jensen, Henry; Helsper, Charles W; Falborg, Alina Z; Glerup, Henning; Gronbaek, Henning; Vedsted, Peter
Abstract: Background: Abdominal cancers represent 30% of all diagnosed cancers. Nevertheless, it is unknown if the general practitioner's (GP's) initial cancer suspicion varies for different abdominal cancer types and how this is associated with referrals to standardized cancer patient pathways (CPPs). Objectives: To explore initial cancer suspicion in GPs and to investigate how this was associated with GP referrals to CPPs and the duration of the primary care interval (PCI) in 10 different abdominal cancer types. Methods: We conducted a cohort study on 1104 incident abdominal cancer patients diagnosed in Denmark in 2016 using a combination of survey and register-based data. Poisson regression was used to estimate associations between GP cancer suspicion, CPP referral and PCI duration. Results: The GPs initially suspected cancer or other serious disease in 46–78% of cases, lowest in kidney cancer, and referred 35–65% to a CPP, lowest in oesophageal cancer. The GP's suspicion at the first presentation was strongly associated with referral to a CPP. The median (0–11 days) and 75th percentile (3–32 days) PCIs varied between the abdominal cancer types. The likelihood of a long PCI was more than 3-fold higher when the GP did not initially suspect cancer. Conclusion: In up to half of abdominal cancer patients, there is no initial suspicion of cancer or serious disease. CPPs were used in only one-third to two-thirds of patients, depending on cancer type. For kidney cancer, as well as several abdominal cancers, we need better diagnostic strategies to support GPs to enable effective and efficient referral. Lay Summary: This study investigates how often a suspicion of cancer is raised by the general practitioner (GP) at the first consultation leading up to a diagnosis for several abdominal cancer types. The study also explores how often the GPs refer these patients to a cancer patient pathway (CPP). Moreover, the length of the primary care interval is measured, that is, the interval from the first time when the patient presents with symptoms to their GP until referral to a hospital or another specialist. The results show that the GPs initially suspected cancer or other serious disease in 46–78% of 10 selected types of abdominal cancer; lowest suspicion was seen for kidney cancer, and referred 35–65% to a CPP; lowest CPP use was seen for oesophageal cancer. The median time from the first visit to the GP until referral to a hospital or another specialist was 0–11 days, depending on the cancer type. The most important factor for a prompt referral was the GP's initial cancer suspicion; this was seen independent of the diagnosed cancer type. These findings call for the development of new cancer pathways that better target the patients in whom the GP does not initially suspect cancer.